2020
DOI: 10.3389/fmicb.2019.03008
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Analysis Reveals Contributions of Citric and Citramalic Acids to Rare Earth Bioleaching by a Paecilomyces Fungus

Abstract: Conventional methods for extracting rare earth elements from monazite ore require high energy inputs and produce environmentally damaging waste streams. Bioleaching offers a potentially more environmentally friendly alternative extraction process. In order to better understand bioleaching mechanisms, we conducted an exo-metabolomic analysis of a previously isolated rare earth bioleaching fungus from the genus Paecilomyces (GenBank accession numbers KM874779 and KM 874781) to identify contributions of compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…(Franz et al 1991;Bosecker 1997;Ambreen et al 2002;Adeleke et al 2010), Aspergillus spp, (Brisson et al 2016;Din et al 2020) and Paecilomyces spp. (Brisson et al 2016(Brisson et al , 2020. Bacterial species include Acinetobacter, Pseudomonas and Bacillus spp.…”
Section: Organotroph Microorganismsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Franz et al 1991;Bosecker 1997;Ambreen et al 2002;Adeleke et al 2010), Aspergillus spp, (Brisson et al 2016;Din et al 2020) and Paecilomyces spp. (Brisson et al 2016(Brisson et al , 2020. Bacterial species include Acinetobacter, Pseudomonas and Bacillus spp.…”
Section: Organotroph Microorganismsmentioning
confidence: 99%
“…(c) During redoxolysis, metal solubilization is promoted by its enzymatic oxidation or reduction, while in (d) bioaccumulation the soluble metal ions can be transported through the cell membrane and accumulate as solid particle within the cell or in vacuoles (Asghari et al 2013 ; Srichandan et al 2019 ). The organic acids identified to be associated with bioleaching include citric acid, gluconic acid, oxalic acid, citramalic acid, acetic acid, succinic acid and itaconic acid (Gadd 1999 ; Adeleke et al 2010 ; Amin et al 2014 ; Brisson et al 2016 , 2020 ). Fungal bioleaching species include, but is not limited to, Penicillium spp.…”
Section: Space Biomining Principlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to siderophores, the production of organic acids such as aliphatic (citrate and oxalate) and aromatic (gluconic, malic, phthalate and salicylate) acids by microbes has been used as a method to leach metals of economic interest such as REE from diverse sources (Figure 8.1) (Barnett et al, 2018;Brisson et al, 2020). For instance, Brisson et al (2020) demonstrated that the fungus Paecilomyces could bioleach up to 42 mg/L of REE from monazite ore using organic acids (i.e., citric and citramalic acids). Similarly, gluconic acids produced by the bacterium Gluconobacter oxydans effectively leached REE (in the order of Y .…”
Section: Microbial Recovery Of Rare Earth Elements 821 Bioleachingmentioning
confidence: 99%
“…Fungus from the genus Paecilomyces produces several metabolites potentially associated with bioleaching, and citric and citramalic acids present a significant contribution to REEs dissolution, 6.4 and 15.0 mg l −1 total REEs solubilized respectively. Furthermore, citramalic acid exhibits more interesting properties to those of citric acid due to the lower radioactive thorium release [32].…”
Section: Bioleaching Of Rees Mineral Oresmentioning
confidence: 99%